2021
DOI: 10.1177/0309524x211060552
|View full text |Cite
|
Sign up to set email alerts
|

A generalized computational approach to predict high-frequency acoustic pressure response of cavity structures for structural health monitoring of wind turbine blades

Abstract: This paper details the development of a generalized computational approach that enables prediction of cavity-internal sound pressure distribution due to flow-generated noise at high frequencies. The outcomes of this research is of particular interest for development of an acoustics-based structural health monitoring system for wind turbine blades. The methodology builds from existing reduced-order aeroacoustic modeling techniques and ray tracing based geometrical acoustics and is demonstrated on the model NREL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The authors confirmed that the proposed method can detect hole-type damage with a diameter of 0.32 cm and crack damage with a length of 1.27 cm. Traylor et al [146] proposed a generic computational method capable of predicting the sound pressure distribution within the blade cavity affected by noise generated by highfrequency flow and conducted an example study on a 5 MW wind turbine blade model. The results show that the proposed method can successfully detect damage in the front half of the blade cavity at the root position of the wind turbine blade.…”
Section: Wind Turbine Blade Damage Detection Based On Beamforming or ...mentioning
confidence: 99%
“…The authors confirmed that the proposed method can detect hole-type damage with a diameter of 0.32 cm and crack damage with a length of 1.27 cm. Traylor et al [146] proposed a generic computational method capable of predicting the sound pressure distribution within the blade cavity affected by noise generated by highfrequency flow and conducted an example study on a 5 MW wind turbine blade model. The results show that the proposed method can successfully detect damage in the front half of the blade cavity at the root position of the wind turbine blade.…”
Section: Wind Turbine Blade Damage Detection Based On Beamforming or ...mentioning
confidence: 99%